Beyond the lecture: a flipped class approach to paralegal education - Stasiewich, Ashley (My University, 2025)
In Canada, paralegal education lacks comprehensive pedagogical research in effective instructional models. Historically, paralegal programs focus on clerical skills, neglecting higher-level legal comprehension and analytical abilities that are vital for a paralegal role in the workforce. This research addresses this gap by exploring the implementation of a flipped classroom approach in an Alberta university that offers paralegal education. This study evaluated whether a flipped classroom in a legal technology course could enhance engagement and understanding of fundamental legal principles among paralegal students, compared to lecture-based models in other previously experienced university courses. Survey data collected through a mixed methods approach in April 2024 revealed that most participants believed that the flipped classroom encouraged participation, felt more confident in applying legal concepts, and were better prepared for the workforce. By examining the impact of flipped classrooms on paralegal education, this research provides insights that can inform curriculum development, address paralegal training challenges, and ensure the acquisition of necessary competencies for success in the legal industry.
Keywords: paralegal education; flipped class; engagement; pedagogy; law